Sensorineural Hearing Loss and Cochlear Outer Hair Cell Function Nasopharyngeal Carcinoma Due to Influence of Cisplatin - Fira Sofia; H.M.S Wiyadi; Achmad Chusnu Romdhoni (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Nasopharyngeal carcinoma is a type of tumor sensitive to chemotherapy and radiotherapy.One of the various chemotherapy drugs is cisplatin. However, the cisplatin effects on sensorineuralhearing loss and cochlear outer hair cell dysfunction in patients with nasopharyngeal carcinoma have notbeen evidently discovered. Objective: This research aims to prove the cisplatin effects on sensorineuralhearing loss and cochlear outer hair cell dysfunction in patients with nasopharyngeal carcinoma.Materials and Methods: This research adopted analytical observation by employing a prospectivecohort study approach. In addition, the sampling technique implemented consecutive sampling. Thisresearch was conducted at the ENT-HN Outpatient Unit (URJ) of the Neuro-otology Division ofDr.Soetomo Public Hospital during September-November 2020 period. The auditory test was executedby Pure-Tone Audiometry (ANM) and Distortion Product Otoacoustic Emission (DPOAE). Meanwhile,the statistical analysis was assessed by the Wilcoxon and McNemar test. Results: This research involved22 samples. The cumulative dose of cisplatin up to chemotherapy series III ranged from 260-270 mgwith an average of 265.45+5.10 mg. The results of the ANM test before and after chemotherapy seriesIII employing Wilcoxon test indicated significant differences in frequency of 500 Hz (p-value =0.014),6000 Hz (p-value = 0.011), 8000 Hz (p-value = 0.019),10000 Hz (p-value = 0.000), and 12500 Hz(p-value = 0.002). The frequency of 125 Hz with a p-value = 0.343, the frequency of 250 Hz with ap-value = 0.690, the frequency of 1000 Hz with a p-value = 0.179, the frequency of 2000 Hz with ap-value = 0.459, and the frequency of 4000 Hz with a p-value = 0.125 indicated no significant differencewitha p-value greater than 0.05. Meanwhile, the DPOAE test results before and after chemotherapyseries III utilizing the McNemar test demonstratedthe frequency of 1000 Hz (p-value = 1.000), 2,000Hz (p-value = 0.453), 4000 Hz Hz (p-value = 1.000), 6000 Hz (p-value = 0.388), 8000 Hz (p-value =0.754), and 1000 Hz (p-value = 1.000). The comparative analysis of the DPOAE test results before andafter chemotherapy Series 3 suggested no significant difference, with a p-value greater than 0.05 at allfrequencies. Conclusion: There were cisplatin effects on sensorineural hearing loss in patients withnasopharyngeal carcinoma after chemotherapy series 3 based on ANM test at the frequencies of 500Hz, 6000 Hz, 8000 Hz, 10000 Hz, and 12500 Hz. There were no cisplatin effects on cochlear outer haircell dysfunction in patients with nasopharyngeal carcinoma after chemotherapy series 3.